A perspectiva ambiental no ensino de História em São João de Pirabas-Pa - MAGNO, Gizelle Albuquerque (2024)
The present work proposes to analyze the Environmental Perspective in History Teaching in schools in the city of São João de Pirabas/PA, using questionnaires to interview teachers who work in the area. With the production of this article, we intend to understand the problems and challenges that History teachers face when incorporating Environmental Education into their classes, because although they recognize the importance of teaching in line with this perspective, there are many challenges. This work also aims to understand what definitions History teachers have about nature and the environment within educational practice, whether they relate the contents of the program curriculum with the environmental theme, whether they problematize environmental modifications by relating them to local history, if there is any proposal in the pedagogical political plan of the school where they work and/or projects on the topic, in addition to understanding which disciplines are involved in these proposals. Therefore, it is important to know the educational discussions about the environmental perspective in the teaching of History in schools in Pirabas.